The effects of non-compliance to taxation and statutory regulations on company financial performance - Mugodhi, Juliet (Midlands State University, 2020)
This research was undertaken to investigate the effects of non-compliance to taxation and statutory regulations on financial performance of Jimat Development consultants. The management report (2017) of Jimat indicated a sharp decrease in profits which was triggered by a rise in costs associated with non-compliance to taxation and statutory regulations. Literature from different sources was reviewed to find out the reasons behind non-compliance, effects of non-compliance on the financial performance of the firm and measures which can be adapted in order to curb non-compliance within the firm. In conducting the study, the researcher used the mixed approach. Questionnaires and interviews were conducted in order to come up with data for addressing the research questions. Data presentation and analysis showed the factors which influence non-compliance, the effects of non-compliance on financial performance and identified the ways which can be implemented in order to curb non-compliance within the firm. The researcher concluded that in order for the company to be compliant so that it can be granted a tax clearance on time and be able to bid for more tenders, the company needs to educate it’s employees on taxation and statutory rules, engage tax consultants and more so to practise proper financial resource management within the company.